HYDRATION OF STRUCTURAL PROTEINS AND MODEL OF CELLULAR PULSATIONS - V.I. Yashkichev (European Scientific Journal, ESJ, 2015)
The turn-to-turn hydration of protein molecules of cytoskeleton, which depends on the temperature, and the concentration of water molecules in a cell is of great importance. The application of hydration increases the volume of a cell. The pressure difference assists in the arrival of sodium ions together with water molecules, oxygen, and nutrients into the cell. However, these substances disturb the homeostasis of the cell. ATP hydrolysis brings about weaker hydration and returns the cell to a point of departure. Therefore, the changes of turn-to-turn hydration are the basis for cell pulsations and other important cell processes. At the same time, the changes of turn-to-turn hydration explain the conversion of heat energy into work.